Benthic dissolved organic carbon fluxes in a drinking water reservoir. (3rd November 2015) - Dadi, Tallent; Friese, Kurt; Wendt‐Potthoff, Katrin; Koschorreck, Matthias
Abstract: The trend of increasing dissolved organic carbon (DOC) in surface waters motivated us to gain a mechanistic understanding of DOC exchange at the sediment water interface in lakes. We quantified seasonal DOC and solute fluxes under different redox conditions, in a small drinking water reservoir using sediment core incubations. Processes governing benthic DOC exchange were microbial production of DOC and interaction with mineral surfaces. Mobilization of DOC in anoxic sediments seemed to be closely linked to reductive dissolution of ferric minerals as shown by the strong positive correlation ( r 2 = 0.99) between DOC and Fe fluxes. Oxidized surface sediments were an efficient DOC trap where DOC was bound to ferric minerals. Redox conditions appeared to be the primary regulator of the DOC exchange, resulting in sedimentary uptake of DOC (−1.8 mmol m −2 d −1 ) only under oxic conditions. DOC production was regulated by temperature, leading to higher DOC fluxes (up to 2.4 mmol m −2 d −1 ) in summer. The sediment was a net sink of DOC (−0.2 tonnes yr −1 ) but this was small compared with the annual DOC load (15 tonnes yr −1 ) of the reservoir. However, the benthic DOC flux was about 10–20% of the dissolved carbon flux at the sediment–water interface, making it a significant process in the lake internal carbon cycle. Climate change is supposed to promote reducing conditions at the bottom of lakes, which might increase benthic DOC production in the future.